LPTO-05. FACTORS INFLUENCING RISK OF LEPTOMENINGEAL METASTASIS IN BREAST CANCER PATIENTS RECEIVING STEREOTACTIC RADIOSURGERY FOR LIMITED BRAIN METASTASES. (12th August 2019) - Zhang, Michael; Chan, Jason; Xu, Chelsea; Anderson, August; Lazar, Ann; Villanueva-Meyer, Javier; McDermott, Mike; Melisko, Michelle; Sneed, Penny; Morin, Olivier; Braunstein, Steve
Abstract: Leptomeningeal metastasis (LM) is a late stage manifestation of advanced breast cancer frequently managed with whole brain radiotherapy (WBRT) and/or intrathecal chemotherapy. A subset of breast cancer patients who undergo stereotactic radiosurgery (SRS) for limited brain metastases (BM) ultimately develop LM. We hypothesized that this subset of high-risk patients may be identified by patient, disease, and/or treatment parameters. Clinical records from 135 consecutive breast cancer patients from a single institution who underwent SRS for BM between February 2010 and March 2018 were retrospectively analyzed. Diagnosis of LM was determined radiographically and/or by cerebrospinal fluid analysis. Demographic data, clinical history, histopathology, BM features, systemic disease burden, and prior treatments were analyzed with Cox proportional hazards regression. In our cohort, 22 (16.3%) patients ultimately developed LM. With a median follow up of 18.9 (IQR 8.6–38.7) months after diagnosis of BM, the actuarial rate of LM at 18 months was 14.5% (95% CI, 7.0–21.4%). Median OS after diagnosis of LM was 7.3 (95% CI, 3.1–15.4) months. There was significantly increased risk of LM with ≥5 vs < 5 BM at BM diagnosis (33.0% vs 7.5% [18-month actuarial risk], HR 3.5, p=0.0045), and ≥7 vs < 7 cumulative number of BM treated (21.9% vs 11.1% [18-month actuarial risk], HR 2.7, p=0.023). Variables not significantly associated with the risk of LM included tumor receptor status (ER, PR, HER2, triple negative), graded prognostic assessment, KPS, extracranial metastases, total BM volume, prior WBRT, or prior surgical resection. In conclusion, patients with a larger number of brain metastases at BM diagnosis or ≥7 cumulative number of brain metastases treated appear to be at higher risk of developing LM and may benefit from stronger consideration of WBRT, intrathecal chemotherapy, and/or brain-penetrating systemic therapy.